Leptin accelerates BMSC transformation into vertebral epiphyseal plate chondrocytes by activating SENP1‐mediated deSUMOylation of SIRT3. Issue 2 (13th January 2023) - Li, Xiaomiao; Fu, Xiaodong; Li, Hao; Gao, Yingjian; Wang, Weili; Liu, Zude; Shen, Yi
Abstract : Bone marrow mesenchymal stem cells (BMSCs) are capable of multidirectional differentiation, and engrafted BMSCs can be used to replace damaged chondrocytes for treatment of intervertebral disc disease. However, chondroblast differentiation of implanted BMSCs is inhibited by the anoxic environment of the articular cavity. Here, we found that leptin enhanced the transformation of BMSCs into chondrocytes under hypoxic conditions. BMSCs isolated from mice were cultured in medium supplemented with leptin under hypoxia. The expression of MFN1/2 and OPA1 were increased only in BMSCs cultured in an anoxic environment. In addition, in hypoxic environments cell energy metabolism relies on glycolysis regulated by leptin, rather than by mitochondrial oxidation. The expression of the de‐SUMOylation protease SENP1 was elevated, leading to SIRT3‐mediated activation of PGC‐1α; these processes were regulated by CREB phosphorylation, and promoted mitochondrial fusion and cell differentiation. The chondrogenic activity of BMSCs isolated from SIRT3 ‐knockout mice was lower than that of BMSCs isolated from wildtype mice. Implantation of SIRT3 ‐knockout murine‐derived BMSCs did not significantly improve the articular cartilage layer of the disc. In conclusion, the hypoxic microenvironment promoted BMSC differentiation into chondrocytes, whereas osteoblast differentiation was inhibited. SENP1 activated SIRT3 through the deSUMOylation of mitochondria and eliminated the antagonistic effect of SIRT3 acetylation on phosphorylation. When phosphorylation activity of CREB was increased, phosphorylated CREB is then transferred to the nucleus, affecting PGC‐1α. This promotes mitochondrial fusion and differentiation of BMSCs. Leptin not only maintains chondrogenic differentiation homeostasis of BMSCs, but also provides energy for differentiation of BMSCs under hypoxic conditions through glycolysis. Abstract : Leptin mediates the transformation of BMSCs into chondrocytes under hypoxia. This process depends on SENP1 to remove SUMO of SIRT3 and activate SIRT3 deacetylase. Activated SIRT3 promotes translocation of phosphorylated CREB into the nucleus and indirectly initiates PGC‐1α.